Microfungal Biomass in the Understorey Soils of Some Arid Zone Trees - Sundarmoorthy, S; Ramchandani, Anu; Jha, Neelu (Annals of Arid Zone, 2016)
Agar film technique was used to study the ecology of microfungal biomass and efficiency of carbon immobilization in the understorey soils of Acacia tortilis. Azadirachla indica. Prosoflis cineraria and Prosopis juliflora. The tree species play a major role in the population and the growth of microfungal hyphae in their understorey soils. A. indica and P. cineraria understorey soils recorded higher microfungal biomass and more efficient immobilization as compared to those recorded by A. tortis and P. juliflora.